If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + x(53) + 8 = 52 Reorder the terms for easier multiplication: 5 + 53x + 8 = 52 Reorder the terms: 5 + 8 + 53x = 52 Combine like terms: 5 + 8 = 13 13 + 53x = 52 Solving 13 + 53x = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 53x = 52 + -13 Combine like terms: 13 + -13 = 0 0 + 53x = 52 + -13 53x = 52 + -13 Combine like terms: 52 + -13 = 39 53x = 39 Divide each side by '53'. x = 0.7358490566 Simplifying x = 0.7358490566
| -3x^2-6x-21=0 | | 13x+3=23+3x | | 7m(m-1)=3(1-m) | | g(b+8)=8x+5 | | (2w-5)w=33 | | X-3-3x=-3(1+x) | | (3x^2+22x-16)= | | -4(x+7)=4(-x+8) | | 12x^2+5x-98=0 | | g(-4b)=8x+5 | | 5(3n+5)+6(1-5n)=16 | | -5(x-4)+7(x-1)=23 | | x^2-20x+51= | | -x^2-12x-9=0 | | 6x+7=2x | | -8(a-1)-(a+4)=-14 | | g(-4)=8x+5 | | 15+x-(x*.10)=8+x | | 7(x-2)+3(x+2)=5x-30 | | -9+18n=-9(-3n-18) | | (y-3)(y-3)=2y^2-5y+3 | | 25h^2=16 | | 12x^2=8x-1 | | 4(-1-15j)=3(-20j-10) | | (v+3)(v+3)=2v^2-2v+24 | | (4x-1)(x+5)=11x+16 | | 3(3x-9)+2(4x+10)= | | 15+x+(x*.10)=8-x | | g(0)=8x+5 | | (v+6)(v+6)=2v^2+6v+29 | | -6(x-2)=-4-4x | | 16-2e=-4e--5-e |